Biocompatible polymers via aqueous electrochemically mediated atom transfer radical polymerization. Issue 1 (2nd January 2020) - Michieletto, Alessandro; Lorandi, Francesca; De Bon, Francesco; Isse, Abdirisak Ahmed; Gennaro, Armando
ABSTRACT: The preparation of well‐defined polymers via aqueous atom transfer radical polymerization (ATRP) is challenging due to the high activity and limited stability of ATRP catalysts in water. Optimized conditions previously reported for the ATRP of some water‐soluble monomers cannot be regarded as universal conditions. Indeed, well‐controlled electrochemically mediated ATRP ( e ATRP) of oligo(ethylene oxide)methyl ether acrylate (OEOA) and 2‐hydroxyethyl methacrylate (HEMA) were achieved by adjusting the conditions in relation to the solubility and reactivity of these monomers and corresponding polymers. Importantly, PEOA with low dispersity and predetermined molecular weight was obtained even with low catalyst loading and high monomer content (up to 50 vol %). Moreover, >90% conversion of HEMA was obtained within 6–7 h, giving PHEMA with dispersity 1.2–1.3. This work confirms e ATRP as a versatile, clean technique applicable to a range of water‐soluble, biocompatible monomers. © 2019 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 114–123 Abstract : Electrochemically mediated atom transfer radical polymerization ( e ATRP) is a powerful technique enabling controlled radical polymerization in notoriously difficult reaction media. Well‐defined polymers with low dispersity can be obtained by copper‐catalyzed e ATRP of oligo(ethylene oxide)methyl ether acrylate and 2‐hydroxyethyl methacrylate at high monomer conversions in aqueous media. Each monomer requires further refining of general guidelines previously reported for controlled aqueous ATRP, such as nature of the ligand, concentration of halide ions, monomer/water ratio, and so forth.